Construction of a Unified Wave-Field Theory Based on Unified Complex Systems Theory and Bohmian Mechanics - Cui, Weicheng; Pan, Lingli (European Journal of Applied Sciences, 2026)
As two core concepts in physics, waves and fields have evolved alongside the advancement of modern physics: originating from mechanical oscillations and Newtonian action-at-a-distance in classical mechanics, they later developed into wave-particle duality and triggered the field-theory revolution within quantum mechanics. Their intrinsic interconnection has long stood as a pivotal research target for physicists pursuing a unified physical framework. This study adopts Unified Complex Systems Theory (UCST) as its ontological backbone and incorporates the realist philosophical underpinnings of Bohmian Mechanics (BM), strictly abiding by the fundamental scientific premise that physical research is confined to observable phenomena. It establishes an integrated theoretical framework unifying waves and fields from four core dimensions: ontological definition, categorization of material existential forms, the intrinsic nature of fundamental interactions, and the consistent logical linkage among waves, particles and physical fields. By retracing the historical developmental trajectory of wave and field definitions, this work reviews prominent cognitive misconceptions formed during the conceptual evolution from the combined perspective of UCST and BM, remedies the theoretical limitations embedded within conventional physical frameworks, and puts forward a core argument: waves arise from the collective coordinated motion of massive particles, whereas fields function as the underlying interaction mechanism governing wave propagation. This work thus achieves triple-layer unification of waves and fields at the levels of kinematic forms, interaction mechanisms and material carriers, offering an original research paradigm for the ongoing development of grand unified physics.